2022
DOI: 10.1002/cnl2.8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalytic nitrate reduction to ammonia using plasma‐induced oxygen vacancies in CoTiO3 − x nanofiber

Abstract: Electrochemical nitrate (NO3−) reduction is a green and economic route for ammonia (NH3) synthesis. However, this conversion suffers from low NH3 selectivity due to strong competition from other NO3− reduction pathways. Here, we report that a plasma‐induced defective CoTiO3 − x nanofiber with oxygen vacancies acts as an efficient electrocatalyst for NO3− reduction to NH3. In 0.1 M NaOH solution containing 0.1 M NO3−, it is capable of achieving a remarkable NH3 yield of 30.4 mg h–1 mgcat.–1 and a high Faradaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Recently, our group reported that CoTiO 3− x nanofibers with oxygen vacancies showed an NH 3 formation rate of 30.4 mg h −1 mg −1 and a large FE of 92.6% in 0.1 M NaOH solution containing 0.1 M NO 3 − . 136 The CuWO 4 hollow nanospheres with oxygen vacancies showed a high NH 3 FE of 94.6% and yield rate of 5.84 mg h −1 mg −1 at −0.7 V vs . RHE.…”
Section: Efficient No3−rr Electrocatalystsmentioning
confidence: 93%
“…Recently, our group reported that CoTiO 3− x nanofibers with oxygen vacancies showed an NH 3 formation rate of 30.4 mg h −1 mg −1 and a large FE of 92.6% in 0.1 M NaOH solution containing 0.1 M NO 3 − . 136 The CuWO 4 hollow nanospheres with oxygen vacancies showed a high NH 3 FE of 94.6% and yield rate of 5.84 mg h −1 mg −1 at −0.7 V vs . RHE.…”
Section: Efficient No3−rr Electrocatalystsmentioning
confidence: 93%
“…In general, active materials and conductive additives are tightly integrated into the flexible substrate with the assistance of inactive polymer binders among flexible electrodes. The commonly used flexible substrates are mainly divided into three types: carbonaceous materials (CMs), [ 25,26 ] polymer networks (PNs), [ 13,27 ] and modified metal [ 28,29 ] substrates (MMs). Based on the selected flexible substrate, the flexible electrodes could obtain specific properties such as conductivity, mechanical durability, and chemical stability.…”
Section: Interface Challenges and Optimization Strategies In Flbsmentioning
confidence: 99%
“…In subsequent research, it was recognized that the flexible conductive substrate is a superior choice for FLBs because it can replace traditional current collectors, conductive additives, and even binders, reducing the portion of inactive materials and the amount of contact interface. For instance, conductive cellulose nanofiber‐based cathodes, [ 13 ] Ni‐cotton fabric‐based cathodes, [ 12 ] and Si/SiO x ‐based carbon fiber (CF) free‐standing anodes [ 15 ] have been developed.…”
Section: Interface Challenges and Optimization Strategies In Flbsmentioning
confidence: 99%
See 2 more Smart Citations